The Challenges in Conserving the Heritage Based on Conservation Practice of AA Maramis Building in Jakarta - Eryudhawan, Bambang; Andi, Andi (International Journal of Environment, Architecture, and Societies, 2022)
Preserving the originality or maintaining the performance is not a choice in heritage conservation. Both aspects need to be completed as a whole consideration for a decision in the conservation project. Conservation practice becomes more complex and challenging, followed by the change of time and condition. This article aims to identify the challenges of heritage conservation practice based on the conservation practice of the A. A. Maramis building. This study was unique in that it linked architectural components of form-function-meaning with a conservation aspect of A. A. Maramis Building restoration. Employing a descriptive qualitative approach, this article characterizes the issues and challenges. The data were collected through a long observation from the initiation until the final stage of the conservation project. The results display some issues that can be addressed as learned from the conservation project of A. A. Maramis Building in Jakarta are related to building regulation, material, and worker skill. Building regulations related to seismic safety are prepared for new structures. Building regulation should provide tools and guidelines that could save the old historic building, prolong its life, and protect the safety of the user. A number of old materials are demanding to be replaced. The construction industry at the present time failed to support most conservation projects, notably regarding building materials such as good quality timber for beams and planks. Old skills to handle masonry construction and woodworks should be reintroduced in technical schools to support conservation projects of buildings from the colonial period.